Comparison of patient-reported and functional outcomes after transition from traditional upper limb prosthetics to multiarticulating hands in the user with a unilateral transradial amputation. Issue 2 (8th April 2023) - MacEachen, Vincent B.; Davie-Smith, Fiona; Carse, Bruce
Abstract : Background: Multiarticulating hands (MAHs) have been commercially available for over 15 years. Despite this, their cost remains significantly higher than traditional electric hands, and they are not routinely available in many countries. The Scottish Specialist Prosthetic Service within the National Health Service has been prescribing MAHs since 2014. However, the benefits of MAHs provided in clinical settings are not well known. Objectives: This study aimed to compare patient-reported and functional measures in unilateral transradial prosthetic users transitioning from a body-powered or traditional myoelectric prosthesis to a MAH. Study design: This was a retrospective cohort analysis of individuals with a unilateral transradial amputation provided with a MAH. Methods: Of 38 users provided with MAHs, 20 had complete data sets of patient-reported and functional measures before and 6 months after provision. These included Disabilities of the Arm, Shoulder, and Hand; Southampton Hand Assessment Procedure Index of Function; health-related quality of life (EQ-5D-5L Health Index); Trinity Amputation and Prosthesis Experience Scales satisfaction; and Box and Block Test. Results: The mean age was 44 years (SD 16) (n = 20), and 75% were male. There were an 8-unit mean reduction in the Disabilities of the Arm, Shoulder, and Hand ( P = .01) and a 9.5-unit improvement in the Southampton Hand Assessment Procedure IOF ( P = .007) at 6 months after provision. Health-related quality of life did not change ( P = .581). Users reported a four-point improvement in their Trinity Amputation and Prosthesis Experience Scales ( P = .004) and transferred 3.3 blocks more completing the Box and Block Test ( P = .001). Conclusions: The evidence clearly supports continued provision of MAHs to this group of moderate users: the more function the user achieves, the less of a disability they perceive to have.